ChemInform Abstract: Strategies for the Construction of Tetrahydropyran Rings in the Synthesis of Natural Products. Issue 29 (22nd July 2014) - Nasir, Nadiah Mad; Ermanis, Kristaps; Clarke, Paul A.
Abstract Review: 50 refs.